2022
DOI: 10.1186/s13034-022-00499-2
|View full text |Cite
|
Sign up to set email alerts
|

Child, adolescent, and caregiver mental health difficulties and associated risk factors early in the COVID-19 pandemic in South Africa

Abstract: At the onset of the COVID-19 pandemic in early 2020 in South Africa, many safety measures were implemented to protect the lives of the population. Ironically, these same safety measures have negatively impacted on the lives of children and their caregivers resulting in increased mental health problems. This study forms part of the multicountry Co-SPACE (COVID-19: Supporting Parents, Adolescents and Children during Epidemics) study that explores how families are coping during the COVID-19 pandemic, and what car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Across the board, adolescents aged 10 to 17 were less likely to be at risk of emotional problems compared with younger children. A study by Bloom et al 43 also supported this finding, showing that younger children were more negatively affected by lockdown and had more mental health problems than adolescents, including emotional problems, misconduct, and hyperactivity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Across the board, adolescents aged 10 to 17 were less likely to be at risk of emotional problems compared with younger children. A study by Bloom et al 43 also supported this finding, showing that younger children were more negatively affected by lockdown and had more mental health problems than adolescents, including emotional problems, misconduct, and hyperactivity.…”
Section: Discussionmentioning
confidence: 79%
“…Reciprocal relationship between parents' and children's mental health was also seen, especially associated with higher levels of depression, anxiety, and stress. 43 Hence, not only should children be provided with psychological support, but also parents should have access to mental health care and make effort to build healthy parent-child relationships.…”
Section: Impact Of Parents' Mental Health Status Toward Childrenmentioning
confidence: 99%
“…It can be argued that this suggests that more attention is paid to SRH among AGYW compared to other equally pressing health issues such as mental health. On the other hand, there is a growing body of evidence con rming the negative impact of COVID-19 on mental health in younger people in SSA [99]- [103]. For example, a crosssectional study in Burkina Faso, Ethiopia, Ghana, Nigeria, and Tanzania found an association between high levels of depression and anxiety, and self-reported impacts of the pandemic [99].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…Reflecting on the lockdown measures, it is ironic that the same safety measures put in place to protect children, communities and individuals had a negative impact on the lives of children and their caregivers (Bloom et al 2022). The parents, children and children from single-parent families reported an increase in mental health problems (Bloom et al 2022).…”
Section: The Psychological Impact Of the Covid-19 Pandemic And The Re...mentioning
confidence: 99%